Effectiveness of Road Mitigation for Common Toads (Bufo bufo) in the Netherlands - Ottburg, Fabrice G. W. A.; van der Grift, Edgar A. (Frontiers in Ecology and Evolution, 2019)
Roads and traffic may have major impacts on amphibian populations, primarily as a result of amphibian road mortality. A variety of measures have been developed to prevent road mortality of amphibians, such as the construction of fences to keep the animals off the road and amphibian tunnels to provide them a safe passage. We carried out a capture-mark-recapture study to evaluate the performance of two tunnels and permanent drift fences for common toads at a local road in the Netherlands. We found that of the marked toads only 31% used the tunnels to cross the road. We assessed four possible explanations for the fact that a proportion of the toads did not use the tunnels: for toad groups that used the tunnels, as compared to toad groups that did not use the tunnels, (1) the mean distance between the location of first capture and the nearest tunnel was significantly smaller; (2) the mean movement distance along the fence was significantly larger; (3) the number of toad groups that walked in the wrong direction after encountering the drift fence was lower; (4) the mean number of nights between first and last capture of the toad group was significantly higher. Over all study years 28% of the migrating toads - marked and unmarked - that attempted to cross the road ended up on the road pavement, despite the mitigation. Migrating population numbers decreased with about 75% after the mitigation measures were installed. We emphasize that better baseline studies on where toads cross before mitigation and improved knowledge on effects of tunnel design and the distances the animals move along a drift fence are vital to mitigate road impacts properly and maintain viable toad populations. We recommend to base tunnel densities on the mean movement distance of the most critical toads, install drift fences that go well beyond the location where toads cross the road, take appropriate measures at entrance roads and at fence ends and consider alternatives to tunnels and fences, such as the creation of breeding waters on both sides of the road.